SCN1A IVS5N+5 G>A Polymorphism and Risk of Febrile Seizure and Epilepsy: A Systematic Review and Meta-Analysis - Hao, Jindou; Liu, Haiying; Ma, Jiying; Liu, Guosheng; Dong, Guoqing; Liu, Peihui; Xiao, Fei (Frontiers in Neurology, 2020)
Background: Previous studies had investigated the association between polymorphism of IVS5N+5 G>A in SCN1A and the risk of febrile seizure and epilepsy. However, the results were inconsistent. We aimed to conduct a systematic review and meta-analysis to evaluate the association between SCN1A IVS5N+5 G>A polymorphism and risk of febrile seizures and epilepsy. Methods: We searched Embase, Medline, Scopus, and CNKI for studies on the association between SCN1A IVS5N+5 G>A polymorphism and risk of febrile seizures and epilepsy up to 19 Feb 2020. We pooled odds ratios (ORs) and 95% confidence intervals (CIs) by different genetic models. To explore the source of heterogeneity, we performed the subgroup analysis by ethnicity and source of control. Results: We included a total of 12 studies in the meta-analysis. We found a significant negative association between G allele SCN1A IVS5N+5 G>A polymorphism, febrile seizures (G vs. A: OR (95% CI): 0.690 (0.530-0.897); GG vs. AA: 0.503 (0.279-0.908); AG vs. AA: 0.581 (0.460-0.733); GG + AG vs. AA: 0.543 (0.436-0.677); AA + GG vs. AG: 1.309 (1.061-1.615)) and epilepsy (G vs. A: 0.822 (0.750-0.902); GG vs. AA: 0.655 (0.515-0.832); AG vs. AA: 0.780 (0.705-0.862); GG vs. AG + AA: 0.769 (0.625-0.947); GG + AG vs. AA: 0.743 (0.663-0.833); AA + GG vs. AG: 1.093 (1.001-1.193)). The subgroup analysis show the association varied by type of disease, ethnicity, and source of control. Conclusion: The present meta-analysis suggests that G allele in SCN1A IVS5N+5 G>A polymorphism is a protective factor of febrile seizures and epilepsy. It is possible to determine the vulnerability of each individual to develop febrile seizures or epilepsy genotype by these genetic variants. Future studies with better study designs are needed to confirm the results. Study registration: This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO, CRD42020163318).